Dinâmica populacional do budião-verde Sparisoma amplum (Ranzani, 1842) na região do Banco dos Abrolhos - BA. - Xavier, Jéssica Aparecida (2015)
The parrotfishes (Labridae: Scarini) are a monophyletic group with 99 species of herbivorous fishes. They play a key role on coral reefs. They are found most commonly in shallow water, where there is a higher incidence of photosynthetic algae. Sparisoma amplum is the most specialized exponent of this group to pray on Brazilian coral reef, acting on them fitness feeding on calcareous algae . The species occurs from Maranhão state to São Paulo state. Little is known about the biology and the species population trends, therefore this work has addressed the characterization of the species sagitta otolith through morphometrical and morphological analysis and the patterns of age and growth, mortality, maturity, selectivity and longevity of Sparisoma amplum of the Abrolhos Bank region/BA. Samples were obtained from fish landings in the municipalities of Caravelas and Alcobaça between the years 2007 and 2014. The sagitta otoliths of Sparisoma amplum showed continued growth that was related to somatic growth. Was found that the species is long-lived (17 years), have slow growth (K = 0,21; 0,20) and reaches large sizes (Linf = 55,55 cm). Two growth models were compared: von Bertalanffy and Schnute-Richards. The models were competitors. Mortality rates, selectivity and maturity obtained infers that the fishing pressure has contributed to a large fraction of total mortality of the species, but it has been captured after being able to reproduce. The species needs to be taken into account in fisheries systems. It needs more oversight of species landings on the Abrolhos Bank region.